Wavelength conversion based on FWM in a HNLF by using a tunable dual-wavelength erbium doped fibre laser source - Awang, N.A.; Lati, A.A.; Ahmad, Harith; Zulkifli, Mohd Zamani; Ghani, Z.A.; Harun, S.W. (Taylor & Francis, 2011)
In this paper, we propose and demonstrate a cost-effective wavelength converter utilising a highly nonlinear fibre (HNLF) and a tunable dual-wavelength fibre laser as the pump source. The proposed system uses only the pump source and a signal probe to generate a partially degenerate four-wave mixing (FWM) effect. An FWM conversion efficiency of 12 dB is obtained at pump and signal powers at þ13.3 dBm and þ5 dBm, respectively, and it is predicted that a higher conversion efficiency is possible if a high power dual-wavelength fibre laser source is used.